CCL2, CCL8, CXCL12 chemokines in resectable non-small cell lung cancer (NSCLC) - Drosslerova, Marie; Sterclova, Martina; Taskova, Alice; Hytych, Vladislav; Richterova, Eva; Bruzova, Magdalena; Spunda, Miloslav; Komarc, Martin; Koziar Vasakova, Martina (Biomedical papers, 2023)
Background. Complex networks of chemokines are part of the immune reaction targeted against tumor cells. Chemokines influence cancer growth. It is unclear whether the concentrations of chemokines at the time of NSCLC (non-small cell lung cancer) diagnosis differ from healthy controls and reflect the extent of NSCLC. Aims. To compare chemokine concentrations (CCL2, CCL8, CXCL12) in the plasma of patients with resectable NSCLC to those without cancer. To determine whether the chemokine concentrations differ relative to the stage of disease. Methods. Sixty-nine patients undergoing surgery for proven/suspected NSCLC were enrolled. They underwent standard diagnostic and staging procedures to determine resectability, surgery was performed. Forty-two patients were diagnosed with NSCLC, while 27patients had benign lung lesions and functioned as the control group. Chemokine concentrations in peripheral blood were assessed using ELISA. Parametric statistics were used for the analysis of results. Results. There were no differences in plasma chemokine concentrations in NSCLC patients compared to controls. CXCL12 concentrations correlated positively with tumor extent expressed as clinical stage, (mean values: stage I 5.08 ng/mL, SEM 0.59; stage II and IIIA 7.82 ng/mL; SEM 1.06; P=0.022). Patients with NSCLC stages II+IIIA had significantly higher CXCL12 concentrations than controls (mean values: stage II+IIIA 7.82 ng/mL; SEM 1.06; controls 5.3 ng/mL; SEM 0.46; P=0.017). Conclusion. CXCL12 was related to tumor growth and could potentially be used as a biomarker of advanced disease.
Keywords: NSCLC; resectability; chemokine CCL2; chemokine CCL8; chemokine CXCL12; peripheral blood; ELISA method; biomarker